Changes in hairiness of woven fabrics at the production and finishing stages - Krupincová Gabriela; Militký Jiří (Scientific Reports)
Abstract Advances in the textile industry have led to a shift from using empirical experience to design fabrics to using computer-aided systems. Objective fabric properties related to appearance, feel, and comfort are predicted based on the physical models. The look and feel of fabrics are greatly influenced by their complex surface topology, which can be defined by two main properties: roughness and hairiness. In this study, a roughness contactless measurement system originally designed for evaluating only the surface roughness was extended to evaluating the hairiness, which is quantified by spatial parameters obtained by the quadrat method. The modified system of Roughness Contactless Measurement system was applied to assessing work shirts across five production stages, and the experimental results demonstrated variations between gray and treated woven fabrics that could be attributed to shrinkage during water-based processes, subsequent drying under tension, and singeing. The gray and pretreated fabrics exhibited the highest hairiness, which was greatly reduced by singeing and stabilized during the finishing stage by an easy-care treatment.